Avaliação da funcionalidade pós-COVID-19: da tradução à aplicação clínica da escala Post COVID-19 Functional Scale (PCFS) no Brasil - Facio, Carina Araujo de (Universidade Federal de São Carlos, 2025)
Introduction: Post-COVID-19 syndrome, characterized by the persistence of symptoms and functional impairments after the acute phase of SARS-CoV-2 infection, represents a clinical and public health challenge. The Post-COVID-19 Functional Status (PCFS) Scale has emerged as a tool to assess post-COVID-19 functional limitations, but no Portuguese version was available for use in Brazil. Objective: This thesis aimed to translate, culturally adapt, and validate the PCFS Scale for use in Brazil, as well as to explore its clinical applicability in the post-COVID-19 population. Methods: The research was conducted in two phases: (I) translation and cross-cultural adaptation of the PCFS Scale, following international guidelines, and assessment of its measurement properties (construct validity, internal consistency, intra- and inter-rater reliability), using the WHO Disability Assessment Schedule 2.0 (WHODAS 2.0) as a reference; (II) application of the Brazilian version of the PCFS in an online cross-sectional study involving participants with a confirmed diagnosis of COVID-19. Results: The Brazilian version of the PCFS demonstrated excellent internal consistency (α = 0.85), reliability (ICC > 0.8), and strong correlation with WHODAS 2.0 (r = 0.73–0.84). Its clinical application revealed that 40% of the sample exhibited functional impairment, along with a longer duration of symptoms, a greater number of symptoms, and a higher proportion of persistent symptoms. Conclusion: The Brazilian version of the PCFS Scale is valid and reliable for clinical and scientific use, representing a relevant tool for assessing and guiding rehabilitation programs in the post-COVID-19 population in Brazil. This thesis provides support for clinical practice, future research, and public health policies.
Assessment of Post-COVID-19 functioning: from translation to clinical application of the Post COVID-19 Functional Scale (PCFS) in Brazil
Keywords: Infecções por Coronavirus; Síndrome Pós-COVID-19 Aguda; Estado funcional; Especialidade de fisioterapia; Estudo de validação; Coronavirus infections; Post-acute COVID-19 Syndrome; Functional status; Physical therapy specialty; Validation study; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL